1982
DOI: 10.1029/gl009i008p00893
|View full text |Cite
|
Sign up to set email alerts
|

Production of nitric oxide by lightning on Venus

Abstract: The first measurements of the production of nitric oxide (NO) by a laboratory discharge in a simulated Venus atmosphere (CO2 ‐ 96% and N2 ‐ 4%) are presented. The average NO yield over a range of energies was found to be 3.7 ± 0.7 × 1015 molecules joule−1. Simultaneous measurements of carbon monoxide (CO) resulting from the lightning‐induced dissociation of carbon dioxide (CO2) indicated a CO yield of about 4 × 1017 molecules joule−1 (presumably with a comparable yield of atomic oxygen). These measurements sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(17 citation statements)
references
References 32 publications
3
14
0
Order By: Relevance
“…Yung and McElroy, 1979) to as high as 3500 K (e.g. The theoretical NO production rate by lightning for pressurs of 1, 10 and 100 bars over a range of temperatures for mixture of Levine et al (1982), whose experimental result is shown for comparison. These theoretical results were obtained using a thermodynamic equilibrium model based upon a 'freezeout' temperature, the temperature above which the chemical reactions are assumed to be extremely rapid and chemical equilibrium is achieved.…”
Section: Calculations Of Lightning Production Of No Xmentioning
confidence: 97%
See 2 more Smart Citations
“…Yung and McElroy, 1979) to as high as 3500 K (e.g. The theoretical NO production rate by lightning for pressurs of 1, 10 and 100 bars over a range of temperatures for mixture of Levine et al (1982), whose experimental result is shown for comparison. These theoretical results were obtained using a thermodynamic equilibrium model based upon a 'freezeout' temperature, the temperature above which the chemical reactions are assumed to be extremely rapid and chemical equilibrium is achieved.…”
Section: Calculations Of Lightning Production Of No Xmentioning
confidence: 97%
“…We have calculated nitrogen fixation by lightning in a broad range of CO 2 -N 2 mixtures overlapping the experimental work of Levine et aL (1982). Figure 1 depicts the theoretical NO production rate for shock pressures of 1, 10, and 100 bars over a range of temperatures for the mixture of Levine et aL (1982).…”
Section: Calculations Of Lightning Production Of No Xmentioning
confidence: 99%
See 1 more Smart Citation
“…(Levine et al, 1982) for comparison. After calculating lightning flash rates for our 0.1-, 1-, and 10-bar pCO 2 cases, we use this plot to evaluate the lightning-generated NO flux in the troposphere for each case.…”
Section: Photochemical Production Of Noxmentioning
confidence: 99%
“…They follow two separate approaches: (1) a bank of capacitors is discharged into a gas mixture having the components of Venus's atmosphere, and then the byproducts of the discharge are analyzed [Levine et al, 1979[Levine et al, , 1982Borucki et al, 1983]; and (2) a focused laser creates a plasma in the gas mix, and the residual gases are analyzed using mass spectrometers [e.g., Borucki et al, 1996;Jebens et al, 1992]. Most of the experiments based on capacitor discharges were made with short gaps: 5-50 mm and a 1 atm pressure [Levine et al, 1979[Levine et al, , 1982Borucki et al, 1983]. The use of mass spectroscopy in these experiments allowed to quantify the yield of CO and NO produced by the discharge.…”
Section: Introductionmentioning
confidence: 99%